Fulbright Alumni State-led Engagement Talk and Junior Science Camp 2023 / Muhammad Usamah Mohd Ridzuan, Marni Jamil and Aileen Farida Mohd Adam - Mohd Ridzuan, Muhammad Usamah; Jamil, Marni; Mohd Adam, Aileen Farida (Academy of Language Studies, 2023)
Universiti Teknologi MARA Penang branch (UiTMCPP) organised a Fulbright Alumni State-led Engagement Talk with the theme Empowering Excellence Through Fulbright: Insights and Opportunities in hybrid mode on 25 May 2023, which was spearheaded by the program director, Madam Aileen Farida Mohd Adam of UiTMCPP. This event was also supported by Sekolah Menengah Sains Kepala Batas (SMSKB), Penang; Mindanao State University-Iligan Institute of Technology (MSU-IIT), the Philippines; Penang Science Cluster (PSC-Pen), Penang; and Malaysian-American Commission on Educational Exchange (MACEE). The talk commenced with an introductory speech about MACEE and Fulbright programs by Mr. Curtis Johnson, the executive director of MACEE who constantly encouraged all potential candidates to explore the benefits, for both educational and personal developments, of participating in such programs. Associate Professor Chemist Dr. Lee Hooi Ling, a recipient of Fulbright US-ASEAN Visiting Scholar program 2022 at the University of New Mexico, proceeded to feature numerous aspects of her experiences working as researcher in the States including her visit to places of interests, discovery of a new and challenging learning environment and the collaborations sought post-program.